The Learn Together programme (part A): co-designing an approach to support patient and family involvement and engagement in patient safety incident investigations - O’Hara, Jane K.; Ramsey, Lauren; Partridge, Rebecca; Redford, Chris; McHugh, Siobhan; Louch, Gemma; Phillips, Penny; Sheard, Laura; Simms-Ellis, Ruth; Waring, Justin; Langley, Joe (Frontiers in Health Services, 2025)
BackgroundWhilst patients and families can and do support patient safety in several ways, empirical evidence for the specific impact of involvement in patient safety incident investigations and their outcomes, has been limited, with little information about how to undertake involvement meaningfully.AimWe aimed to (i) develop a set of common principles to guide involvement of patients and families in patient safety incident investigations; (ii) develop a working programme theory for how these might be enacted; (iii) co-design guidance to support the meaningful involvement of patients and families in patient safety incident investigations.MethodsWe synthesised three existing data sets (a literature review, a documentary analysis of incident investigation policies and 42 interviews with patients, families, lawyers, incident investigators, and healthcare staff) relating to patient and family involvement in incident investigations. Ten common principles and a working programme theory were drafted. Within a convened co-design community, we then developed guidance for patients, families, staff, and investigators in local NHS Trust and national investigations, via a series of workshops.FindingsWe developed ten ‘common principles” and a working programme theory for an approach that might support meaningful patient and family involvement in incidents investigations. Based on these principles and the programme theory, we co-designed guidance to be used within NHS Trust and national investigations of harm that follow patient safety incidents. The guidance includes information, resources and tools to enable better understanding and practice, from the perspective of patients, families, investigators and staff, on how to be meaningfully involved.ConclusionsOur ten common principles and co-designed guidance emphasise two key things. First, that organizational learning is not the only desired outcome for incident investigations, with patients, families and staff reporting the need for restoration and repair. Second, that investigations can be part of reparation, but when it fails to address the needs of stakeholders arising from investigations, it can compound the harm of the original incident. As a result, we juxtapose existing theories, and illuminate new insights, proposing a theory of “restorative learning”. We see design as an ongoing phenomenon—the guidance is our current iteration, and we learnt several valuable lessons about doing co-design.